How to make mistakes on purpose : bring chaos to your order - Rosenwald, Laurie, 1955- (Hachette Go, 2021)
"Based on her popular workshop, artist, designer and author Laurie Rosenwald reveals her unique approach to coming up with ideas through unconventional creativity hacks and prompts"--